PROGRAM PENGEMBANGAN BIMBINGAN KONSELING UNTUK MENINGKATKAN KECAKAPAN PENGARAHAN DIRI (SELF DIRECTION) PADA MAHASISWA UIN RADEN INTAN LAMPUNG - Fiah, Rifda El (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Students currently in a life full of challenges, the growing need to have an identity and maturation of career choices. Therefore they are expected to be continuously on a variety of changes, diversity of choices, competition, and the demands of relentless self-adjustment, both at the campus, local, national, and global levels. Students who do not have self-direction skills are thought to be experiencing difficulties, anxiety, and are caught up in confusion, uncertainty, immaturity, and developmental stagnation. For this reason, students need to have self-direction skills that include aspects of initiative, autonomy, flexibility, and responsibility that are all needed to carry out the learning process and live life effectively in an effort to achieve goals, fulfill development tasks, and achieve optimal development. This study uses a descriptive approach, which aims to explain a systematically or explain certain fields that are the center of attention of the researcher factually and thoroughly, namely self-direction skills dimensions that students need to have in order to be able to undergo the lecture and effective learning process at the UIN campus. Raden Intan Lampung. The research process is carried out by identifying student self-direction skills and the conditions that PA lecturers need to have to help students have self-direction skills. The next step is to formulate a self-direction skills guidance program. Along with the series of studies referred to, the program was recommended to be carried out at the Raden Intan Lampung UIN FTK.